2022
DOI: 10.1101/2022.09.23.509114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In host evolution of Exophiala dermatitidis in cystic fibrosis lung micro-environment

Abstract: Individuals with cystic fibrosis (CF) are susceptible to chronic lung infections that lead to inflammation and irreversible lung damage. While most respiratory infections that occur in CF are caused by bacteria, some are dominated by fungi such as the slow-growing black yeast Exophiala dermatitidis. Here, we analyze isolates of E. dermatitidis cultured from two samples, collected from a single subject two years apart. One isolate genome was sequenced using long-read Nanopore technology as an in-population refe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…We had previously identified a CF infection predominated by E. dermatiditis. We performed whole genome sequencing of twenty-three isolates and found a subpopulation of isolates with a non-synonymous SNP in the MRS4 (Figure 7A) (31). Subsequent Sanger sequencing confirmed that seven of the twenty three isolates carried an MRS4 ortholog with a sequence identical to the E. dermatiditis type strain, NIH8656 (referred to here as encoding Mrs4 40E-REF ).…”
Section: Mrs4 Mutations In Other Fungi Of Clinical Interestmentioning
confidence: 94%
“…We had previously identified a CF infection predominated by E. dermatiditis. We performed whole genome sequencing of twenty-three isolates and found a subpopulation of isolates with a non-synonymous SNP in the MRS4 (Figure 7A) (31). Subsequent Sanger sequencing confirmed that seven of the twenty three isolates carried an MRS4 ortholog with a sequence identical to the E. dermatiditis type strain, NIH8656 (referred to here as encoding Mrs4 40E-REF ).…”
Section: Mrs4 Mutations In Other Fungi Of Clinical Interestmentioning
confidence: 94%
“…The individual SRA read accession numbers and genome accession numbers for each isolate are listed in Table 1 . Genome assembly, annotation, and TEF1 phylogenetic assessment pipeline and related code are archived in Zenodo ( 40 ).…”
Section: Announcementmentioning
confidence: 99%